Nanoscience and Nanotechnology : Advances and Developments in Nano-sized Materials - Baldi, Livio; Bartolucci, Cecilia; Basu, Bikramjit; Biswas, Kanishka; Borchard, Gerrit; Braegger, Urs; Brock, Thomas H.; Dan, Atasi; Di Francesco, Tiziana; Fechete, Ioana; Fecht, Hans-Jörg; Gluche, Peter; et al. (De Gruyter STEM, 2018)
Innovations in Nanoscience and Nanotechnology summarizes the state of the art in nano-sized materials. The authors focus on innovation aspects and highlight potentials for future developments and applications in health care, including pharmaceutics, dentistry, and cosmetics; information and communications; energy; and chemical engineering. The chapters are written by leading researchers in nanoscience, chemistry, pharmacy, biology, chemistry, physics, engineering, medicine, and social science. The authors come from a range of backgrounds including academia, industry, and national and international laboratories around the world. This book is ideally suited for researchers and students in chemistry, physics, biology, engineering, materials science, and medicine and is a useful guide for industrialists. It aims to provide inspiration for scientists, new ideas for developers and innovators in industry, and guidelines for toxicologists. It also provides guidelines for agencies and government authorities to establish safe working conditions.